How Do Investors Judge the Risk of Financial Items? - Koonce, Lisa; McAnally, Mary Lea; Mercer, Molly (The Accounting Review, 2005)
This paper proposes and tests a risk model that explains how investors perceive financial risks. The model combines conventional decision-theory variables—probabilities and outcomes—with behavioral variables from psychology research by Slovic (1987), such as the extent to which a risky item is new, causes worry, and is controllable. To test our model, we conduct two studies in which M.B.A. students judge the risk of a broad range of financial items. Our results indicate that both the decisiontheory variables and Slovic's (1987) behavioral variables are important in explaining investors' risk judgments. Further, we demonstrate that information about the amount of potential loss outcome contained within mandated risk disclosures not only directly influences risk judgments, but also indirectly affects such judgments via its effect on some of Slovic's (1987) behavioral variables. By identifying this unintended consequence of current risk disclosures, these results have the potential to influence the way accounting regulators, firm managers, and academic researchers think about risk disclosure.